INOVASI PEMBELAJARAN - Dini Putri Haryanto (Perspektif Ilmu Pendidikan, 2007)
Innovation is needed to solve many kinds of problem in human life. Monotony or boredom can be also avoided by creative and innovative ways of doing things. This article describes the importance of innovation in instructional strategies. Four examples of innovation in instructional strategy at school and one example in improving the community welfare are presented and analysed. The article concludes that to succeed the implementation of an innovation, a set of procedures in difusing should be followed properly.